Role of NanoBioSensor of Gallium Phosphide Sheet for Detecting and Removing of Nitric Oxide & Nitrogen Dioxide: Chemisorption Study by DFT Method - (:unkn) unknown (AMG Transcend Association, 2024)
The role of the gallium phosphide nanosheet for the adsorption of pollutant gases of nitric oxide and nitrogen dioxide was investigated by applying density functional theory. The fluctuations of charge distributions have demonstrated a more significant charge transfer between graphitic-like gallium phosphide surface (electron acceptor) and gas molecules (electron donors) through the adsorption process. The partial electron density states related to this have illustrated that the nitric oxide and nitrogen dioxide states in the gallium phosphide nanosheet have more of the conduction band, while the developed contribution of P states are near Ga states, but N and O states have minor contributions. Gallium phosphide nanosurface has indicated enough capability for trapping nitric oxide and nitrogen dioxide through charge transfer from N and O atoms to the Ga atoms due to intra-atomic and interatomic interactions.